THE TRANSITIVITY SYSTEM ANALYSIS ON BANGTAN SONYEONDAN’S (BTS) SPEECH TEXT - Lestari, Tri Puji; Nugraheni, Yunita; Santosa, Budi Tri (Premise: Journal of English Education and Applied Linguistics, 2024)
The Love Myself Campaign, a collaborative project between BTS and UNICEF, is a campaign that voices the importance of loving yourself. As part of the campaign, BTS gave a speech at the 73rd UN General Assembly on September 28, 2018. The researcher used the speech text in this campaign as data in literature research, which was analyzed using a descriptive qualitative method. The study aims to discover how mental health awareness is conveyed through the transitivity system. Systemic Functional Linguistics by M.A.K. Halliday is used as a theory to analyze data, more precisely, the transitivity system in ideological meta functions. This meta function sees language as a symbol of human experience in the real world and the mind. Meanwhile, transitivity is a system that represents human experience as a process. The researcher found three dominators: the mental process (20) showed that the speaker tried to motivate the audience through his or her personal feelings and experiences; the first person "I" (42) showed that the speaker made himself the central subject of the speech. The non-circumstance clause (53) showed that the speech was global. Through these results, it can be concluded that the soft campaign method conveys the concept of mental health awareness in speech.